The case for humble expectations: CEO humility and market performance - Petrenko, Oleg V.; Aime, Federico; Recendes, Tessa; Chandler, Jeffrey A. (Strategic Management Journal, 2019)
Abstract Research Summary In this study, we investigate the effect of chief executive officer (CEO) humility on firm's market performance. We argue and find that firms with more humble CEOs will have better market performance but not because they actually perform better but, rather, because they benefit from an expectation discount in the market. Specifically, we show that, all else equal, financial analysts announce lower earnings per share expectations for firms with more humble CEOs. This expectation discount sets the stage for those firms to meet or beat analysts' expectations resulting in improved market performance for firms with humble CEOs. We find support for our ideas with a sample of Standard & Poor's (S&P) 500 CEOs, operationalizing CEO humility with a videometric technique. Managerial Summary In this study, we investigate the effect of CEO humility on firm's market performance. We show that firms with more humble CEOs will outperform other firms in the market because financial analysts tend to set lower market expectations for firms with more humble CEOs increasing the probability that they will outperform those expectations. Rather counterintuitively, these firms do not have better market performance because they perform better but because they face lower expectations. Ultimately, the study demonstrates the importance of CEO characteristics for external evaluations and perceptions about the firm with significant effects on investment performance.